Guidelines on the Inclusion and Protection of Adolescent Minors and Young Adults in Health Research: A Position Statement of the Society for Adolescent Health and Medicine (Journal of adolescent health, 2025)
These guidelines aim to assist researchers and research ethics committees/institutional review boards in the ethical conduct of health research with adolescents and young adults (AYA), particularly research with adolescent minors. Inclusion of AYA in research and protection from research harms are essential if, as individuals and as a group, they are to receive the benefits of research. The ethical principles of respect for persons, beneficence, and justice, the human rights concepts of best interests and emerging capacity, and the concept of appropriate inclusion collectively provide an ethical framework for evaluating the circumstances within which adolescent minors can and should be involved as research participants. Likewise, legal concepts guiding informed consent in health-care practice—age of majority, emancipation, mature minor, and minor consent—provide an important conceptual basis for informed consent with adolescents in health research. Consent processes in adolescent health research should be based on scientific understandings of AYA cognitive, psychological, and social development; the weight of current scientific evidence suggests that capacity to provide informed consent for research is present by the age of 14 years. When adolescent minors consent for themselves (i.e., autonomously or independent of parents/guardians), procedures should be in place to assess and support their desire for advice from parents and other trusted adults. Researchers should involve AYA in the codesign of research and should involve community members, parents, and AYA in the development of research priorities and questions, to ensure that research is relevant to AYA, to protect privacy and confidentiality, to facilitate the dissemination of research findings, and to promote translation of research into practice. Research with AYA should never reinforce stigma and discrimination of AYA or the groups to which they belong.